Lowbush blueberry fruit yield and growth response to inorganic and organic N-fertilization when competing with two common weed species. - Charles Marty; Josée-Anne Lévesque; Robert L Bradley; Jean Lafond; Maxime C Paré (PLoS ONE)
Inorganic N fertilizers are commonly used in commercial blueberry fields; however, this form of N can favor increased weed species' growth, which can ultimately reduce the benefits of fertilization. We hypothesized that chipped ramial wood (CRW) compost is an effective alternative organic fertilizer for blueberry plants when weeds are present, as ericaceous shrub species are generally more efficient in utilizing organic N than herbaceous weed species. In this study, we measured the growth, fruit yield, and foliar N response of lowbush blueberry (Vaccinium angustifolium Aiton) to an application of 45 kg N ha-1 in the form of organic (CRW) or inorganic N (ammonium sulfate) in two areas of a commercial field colonized by either poverty oat grass (Danthonia spicata (L.) Beauv.) or sweet fern (Comptonia peregrina (L.) Coult.). We also assessed the impact of the fertilization treatments on litter decomposition rates. Contrary to our hypothesis, we found no significant increase in blueberry fruit yield or growth using CRW. By contrast, inorganic N-fertilization increased fruit yield by 70%. The effect was higher in the area colonized by D. spicata (+83%) than by C. peregrina (+45%). Blueberry fruit yield was on average twice higher in the area of the field having D. spicata than C. peregrina, suggesting a stronger competition with the latter. However, the increase in D. spicata density from 0-1 to >25 plants m-2 reduced fruit production by three-fold and strongly impacted vegetative growth in both fertilized and unfertilized plots. The impact of increased C. peregrina density was comparatively much lower, especially on vegetative growth, which was much higher in the area having C. peregrina. These patterns are likely due to a lower competition for N uptake with C. peregrina as this species can derive N from the atmosphere. Interestingly, the higher fruit yield in the area colonized by D. spicata occurred even in plots where the weeds were nearly absent (density of 0-1 plant m-2), revealing the influence of unidentified variables on blueberry fruit yield. We hypothesized that this difference resulted from over-optimal foliar N concentrations in the area colonized by C. peregrina as suggested by the significantly higher foliar N concentrations and by the negative correlation between foliar N concentrations and fruit yields in this area. The possibility of an influence of C. peregrina on flowering and pollination success, as well as of unidentified local site conditions is discussed. The tested N-fertilization treatments did not affect foliar N concentrations or litter decomposition rates. Overall, our results show that ammonium sulfate is very effective at increasing fruit yields but that both fruit yields and the efficiency of the N-fertilization treatment are decreased by increased D. spicata density, especially above 25 plants m-2. Although CRW did not significantly enhance fruit yields in the short term, this fertilizer may have a long-term beneficial effect.